From the Dictionary of Artists of the Peoples of the USSR to the Dictionary of Artists of the Peoples of Russia - Evsevyev, Mikhail Yu.; Sokhor , Tatiana E. (Actual Problems of Theory and History of Art, 2023)
The article gives an overview of the history of the creation of a biobibliographical dictionary dedicated to the domestic masters of arts and contains a review of new volumes (‘F’ and ‘X’) of the biobibliographical dictionary ‘Artists of Peoples of Russia 11th–21st centuries’ published by the Research Institute of the Russian Academy of Arts in 2021–2022. An attempt to create a consolidated dictionary of Russian artists was made in the 19th century by Nikolay Sobko (1851–1905), but was interrupted by the death of the author. The second attempt to continue this work is associated with the name of Oskar Wolzenburg (1886–1971), who tried to create a dictionary before World War II. After the war, four books of the Wolzenburg Dictionary published in the 1970s and early 1980s remained as fragments of the project. The sequel followed at the turn of the 20th and 21st centuries. This included the release of two additional books and the reissue of a set of 5 volumes (6 books). Again, the difficult geopolitical situation interrupted the continuation of the publication. However, the work on the dictionary of artists did not stop, although the methodology of the new generation of dictionaries underwent serious changes.